ANALYSIS OF FACTORS AFFECTING THE INCIDENCE OF PERINEAL RUPTURE AT THE CIRINTEN HEALTH CENTER IN LEBAK DISTRICT IN 2023 - Rahayu, Rika; Barkah, Asep (HEARTY, 2025)
Background: Perineal rupture occurs in almost all first deliveries and not infrequently also in subsequent deliveries. Perineal rupture is influenced by several factors, namely age, parity, education, occupation, and newborn weight. Objective: to determine the relationship between age, parity, education, occupation, and newborn weight with the incidence of perineal rupture at Cirinten Health Center, Lebak Regency in 2023. Research method: quantitative analytic with cross-sectional design. The research sample was maternity mothers who gave birth at Cirinten Health Center, Lebak Regency in August-October 2023 as many as 55 respondents with a simple random sampling technique. The research instrument used medical record data analyzed using the Chi-Square test. Results: univariate analysis showed that most laboring mothers experienced perineal rupture 56.4%, low-risk age 72.7%, parity > 1 70.9%, low education 67.3%, not working 52.7%, and newborn weight ≥ 2500 grams 85.5%. The results of the bivariate analysis showed a relationship between age (p-value = 0.014), parity (p-value = 0.007), education (p-value = 0.035), work (p-value = 0.024), and newborn weight (p-value = 0.016) with the incidence of perineal rupture. Conclusions and Suggestions: age, parity, education, occupation, and newborn weight are associated with the incidence of perineal rupture. Midwives are expected to minimize the occurrence of perineal rupture in laboring women by establishing cooperation between mothers and midwives during the process of receiving.